2021
DOI: 10.1038/s41598-021-91740-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ocular morphology after cataract surgery in open angle glaucoma patients

Abstract: The purpose of this study was to evaluate intraocular pressure (IOP) pre- and postoperatively, together with anterior chamber angle (ACA) parameters and biometrical results in cataract patients with or without open angle glaucoma (OAG). The prospective observational case–control study included 15 eyes with cataract and OAG in the glaucoma group and 25 eyes with only cataract in control group. Examination included full ophthalmic evaluation, IOP, ocular biometry and anterior segment optical coherence tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…They also found steroid response to be associated with longer axial length regardless of glaucoma status and with more preoperative medications in glaucoma patients. However, absolute IOP reduction at 6 months postcataract surgery was found to be more pronounced in patients with OAG compared with nonglaucomatous eyes in a recent study from Pakuliene et al [46 ▪ ]. They also found that the reduction in IOP did not correlate with preoperative ACA width in either group, and that the axial length was shorter postoperatively in the control group, but remained similar in the OAG group.…”
Section: Postoperative Considerationsmentioning
confidence: 86%
“…They also found steroid response to be associated with longer axial length regardless of glaucoma status and with more preoperative medications in glaucoma patients. However, absolute IOP reduction at 6 months postcataract surgery was found to be more pronounced in patients with OAG compared with nonglaucomatous eyes in a recent study from Pakuliene et al [46 ▪ ]. They also found that the reduction in IOP did not correlate with preoperative ACA width in either group, and that the axial length was shorter postoperatively in the control group, but remained similar in the OAG group.…”
Section: Postoperative Considerationsmentioning
confidence: 86%
“…Furthermore, Pakuliene et al identified a shortening of AL in normotensive eyes and no change in OAG eyes postoperatively. 30 The authors attributed this finding to the difference in scleral rigidity in glaucomatous eyes. In our present study, these findings coincide only with our arm of OAG eyes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 14 ] With the larger pseudophakic posterior chamber, a larger amount of aqueous humor flows from the posterior chamber to the anterior chamber with each ocular movement. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%